Will You Awaken When Your Netflix No Longer Works? American Films, Television Productions and Social Transformations in Poland - Mirosław Filiciak (European Journal of American Studies)
This article is devoted to the historical changes of the status of access to American TV and cinema content in Poland. Using the framework of cultural studies, media are treated here both as texts and objects. The analysis of case studies from the VHS era as well as of contemporary online streaming services connects the way people access video content with the production of social prestige, and shows how changing styles of video consumption mark social transformations in contemporary Poland.